Producción de Membrana de Celulosa Bacteriana a partir del jugo de residuos de cascara de plátano y su aplicación en la filtración de patógenos (2023)
Bacterial cellulose is notable for its versatility in various applications, such as the filtration of contaminated water. However, production costs are high. In this study, banana peels were used as an alternative carbon source, supplemented with several separate nitrogen sources. The membranes obtained were characterized and the filtration process was carried out against E. coli and S. aureus. The medium supplemented with peptone produced better results with 3.17 g/L of cellulose in 10 days.